Palembang City Community Participation in Sports at Gelora Sriwijaya Jakabaring Stadium Palembang - Yusvitadadari, Ardiansyah; Manullang, Jujur Gunawan; Imansyah, Farizal (Journal of Social Work and Science Education, 2023)
This study aimed at determining the level of participation of Palembang society in doing sport at the Gelora Sriwijaya Jakabaring Palembang (GSJP) stadium. The sample was 90 people. The research method used a quantitative descriptive. The sampling in this study was carried out by probability sampling technique, called proportionate stratified random sampling using the Sports Development Index formula. From 90 people sampled divided into age groups: 30 teenagers (12-25 years), 30 adults (26-45 years) and 30 elderly (46-65 years) which is in each age group consisting of 15 males and 15 females. The results of this study concluded that the participation rate index of the people of Palembang city exercising at the GSJP stadium for teenagers got a result of 0.400. This showed that youth sports participation in the city of Palembang was high. For adults, to get a result of 0.533 showed that adult sports participation in the city of Palembang was high. For the elderly, to get a result of 0.333 showed that elderly sports participation in the city of Palembang was high. Overall, this 0.422 result showed that the sports participation of Palembang society was high. One of the SDI indicators that has been studied showed a number in the range of 0.000 - 0.260, meaning that community participation in the city of Palembang was high. So, the community can be consistent and participate in sports by maximizing the use of the GSJP stadium.